Assessing components of uncertainty in demographic forecasts with an application to fiscal sustainability - Juha Alho; Jukka Lassila (The Research Institute of the Finnish Economy (ETLA), 2022)
When the future evolution of demographic processes is described in a stochastic setting, the challenge is to communicate the meaning of forecast uncertainty in an understandable way, to decision makers and public at large. For the purpose of risk communication, a formal setting is developed, in which the roles of the demographic processes on point forecasts and predictive distributions can be elucidated. The communication problem becomes central in fiscal decision making, when eventual forecast errors have differential implications on the value of the policy options being considered. Tax rate that is required to maintain financial sustainability, until a given target year, is used for illustration.
Keywords: J11; J18; H68; 330; Aging; Demography; Predictive distribution; Risk communication; Stationary equivalent population